2014
DOI: 10.1016/j.apcata.2013.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium chloride: A new aluminium source to prepare SAPO-34 catalysts with enhanced stability in the MTO process

Abstract: The MTO process produces lower olefins from natural gas or coal via methanol, providing an interesting route to obtain valuable petrochemicals from carbon sources alternative to petroleum. Small-pore silicoaluminophosphate SAPO-34 has been proven an efficient catalyst for the MTO process, showing exceptionally high selectivity to lower olefins. However, these catalysts undergo rapid deactivation due to deposition of high molecular weight hydrocarbons on the pore entrances, which completely blocks the internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…It has been reported that the deactivation rate was substantially decreased by water addition to the feed. Researchers have attempted to increase the stability of H-SAPO-34, the archetypal MTO catalyst, 39,40 by decreasing the particle size, [41][42][43] creating a secondary network of meso-and macropores 44 and addition of water in the feed [9][10][11]23,45,46 . For H-SAPO-34 catalysts at 400 °C it was reported that an optimal feed consists of 73-80 mol % water to minimize the coking rate and maximize the olefin selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the deactivation rate was substantially decreased by water addition to the feed. Researchers have attempted to increase the stability of H-SAPO-34, the archetypal MTO catalyst, 39,40 by decreasing the particle size, [41][42][43] creating a secondary network of meso-and macropores 44 and addition of water in the feed [9][10][11]23,45,46 . For H-SAPO-34 catalysts at 400 °C it was reported that an optimal feed consists of 73-80 mol % water to minimize the coking rate and maximize the olefin selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…43 As it was mentioned previously, the crystal size has been proven to be a key parameter controlling the catalytic behaviour of zeolitic materials in the methanol transformation to olefins, being possible to enhance significantly the stability of the catalysts by decreasing the crystallite size to the nanometer scale. 22,23,27,47 Besides, it is known for some SAPO materials that the silicon concentration in the synthesis gel influences the size of the obtained crystals. 32 The crystallite size and morphology of the SAPO samples obtained have been studied by scanning electron microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, the particle size and the presence of hierarchical porosity have been widely correlated with the diffusion limitations in the micropores, showing that smaller or mesopore-modified crystals exhibit an enhanced stability in the process. 22,23,[27][28][29][30] Other parameter that strongly affects the catalytic performance is the acidity of the materials. This property depends on the content and distribution of silicon in the SAPO framework; considering the Si distribution as the kind of Si environments formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeolites with shape selectivity, high surface area, and high thermal stability, such as ZSM-5, TS-1, and SAPO-34 [1][2][3][4][5][6][7], are increasingly common in the field of catalysis, because microporous materials with selected properties and functions are in extreme demand in the contemporary chemical industry. SAPO-34, a silicoaluminophosphate zeolite with a large chabazite (CHA) framework structure and small 8-ring pore (0.38 nm 9 0.38 nm), has attracted great attention as a catalyst in a number of reactions, such as hydrogen purification, CO 2 /CH 4 separation, the dehydration of fructose into HMF, and the conversion of methanol-to-olefins (MTO) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%